Porosity of Deep Fat Fried Breaded Chicken Meat - Mladen Brnčić; Suzana Rimac Brnčić; Sven Karlović; Tomislav Bosiljkov; Branko Tripalo; Damir Karlović; Jura Šipušić; Drago Pukec; Damir Ježek (Food Technology and Biotechnology, 2009)
Effects of the addition of rice starch and dietary fibres (pectin and Fibrex) on the porosity of basic frying mixture formulations (corn flour, salt, spices) and oil uptake of coated chicken meat have been evaluated. Porosity of the fried breaded chicken meat was calculated from particle and bulk density. Pore size and particle size distribution were determined using microscopy image analysis and particle density by mercury intrusion porosimeter (MIP). Since there is a wide range of particle diameters, significant differences in pore size distribution were found. Also, pore structure appeared to be affected by oil absorption. Mercury entrapment in pores decreased significantly during 8 min of frying. The obtained results show that porosity of the samples is different for different frying mixture formulations and indicate that there is a difference in the extent of oil uptake for different formulations due to film forming capabilities of dietary fibres (pectin and Fibrex).